Attentional control in Alzheimer's disease. - Baddeley, A; Baddeley, H; Bucks, R; Wilcock, G (2001)
Attentional control of executive function declines during the early stages of Alzheimer's disease. Controversy exists as to whether this decline results from a single global deficit or whether attentional control can be fractionated, with some aspects being more vulnerable than others. We investigated three proposed domains of attention, namely (i) focal attention, based on simple and choice reaction times; (ii) the capacity to resist distraction in a visual search task; and (iii) the capacity to divide attention between two simultaneous tasks. For each domain, two levels of difficulty were used to study Alzheimer's disease patients, who were compared with elderly and young control subjects. The unitary attentional hypothesis predicted that the impacts of level of difficulty, age and disease would be qualitatively similar across the three attentional domains. In fact we observed different patterns for each domain. We obtained no differential impairment for patients in the focal attentional task, whereas patients were somewhat more susceptible than control subjects to the similarity of the distractor items in visual search. Finally, we observed marked impairment in the capacity of Alzheimer's disease patients to combine performance on two simultaneous tasks, in contrast to preserved dual-task performance in the normal elderly group. These results suggest a need to fractionate executive processes, and reinforce earlier evidence for a specific dual-task processing deficit in Alzheimer's disease.